Penerapan Pendekatan Realistic Mathematic Education (RME) dalam Pembelajaran Matematika SMP Ditinjau dari Aktivitas Pembelajaran Siswa - Qhadhavy Putri, Iqlima Khartini; Sutarni, Sri (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to examine the influence of the Realistic Mathematics Education (RME) approach and students' learning activities on mathematics learning outcomes. The method used is a quantitative approach with a true experimental design, comparing an experimental class that received treatment using the RME approach with a control class that received conventional instruction. The population in this study comprised eighth-grade students at SMP Muhammadiyah Al-Kautsar in the 2024/2025 academic year. The sample was randomly selected using a random sampling technique, resulting in class VIII A as the experimental class and class VIII B as the control class, each consisting of 32 students. The material taught was the Pythagorean Theorem. The instruments used in the study were an essay-based learning outcome test consisting of three questions and a student learning activity questionnaire containing 20 statements. Hypothesis testing was conducted using two-way ANOVA with a significance level of 0.05. The results indicated that the significance value for the interaction between the learning approach and learning activity on student learning outcomes was 0.509 (> 0.05), meaning there was no significant interaction between the two variables. However, both the RME approach and learning activities individually had a significant effect on students’ learning outcomes. In conclusion, the application of the RME approach and the improvement of students’ learning activities can individually enhance mathematics learning outcomes. While the combination of these two factors did not show a statistically significant interaction, each contributed positively on its own.   Keywords: RME Approach, Learning Activities, Learning Outcomes, Realistic Mathematics Education.